1984
DOI: 10.1515/bchm2.1984.365.1.633
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Lectins of Bovine Pancreas

Abstract: Affinity chromatography of salt and detergent extracts from bovine pancreas on gly-. cosylated or glycoprotein-linked Sepharose 4B resulted in purification of different carbohydratebinding proteins.Three species of proteins with molecular masses of 16 kDa, 35 kDa and 64 kDa exhibiting specificity for ß-galactosides, but none with preferential specificity for a-galactosides, were isolated from salt and detergent extracts. No Ca 2 ® was required for binding.Mannan-binding proteins of 37 kDa, 47 kDa and 94 kDa wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…More recently, these compounds have been discovered in animals, including mammals (for exhaustive review, see Barondes, 198 1, 1984;Harford, 1982: Olden et al, 1982). Various lectins have been isolated from liver and macrophages (Stahl et al, 1976(Stahl et al, , 1978Kawasaki et al, 1978;Steer and Ashwell, 1980;Stockert et al, 1980;Sahagian et al, 198 1 ;Maynard and Baenziger, 1982;Mori et al, 1983;Wild et al, 1983;Gabius et al, 1984;Roche et al, 1985). It has been suggested that proteins with carbohydrate binding properties of different specificities exist in the CNS (Kobiler and Barondes, 1977;Simpson et al, 1977;Gremo et al, 1978).…”
mentioning
confidence: 99%
“…More recently, these compounds have been discovered in animals, including mammals (for exhaustive review, see Barondes, 198 1, 1984;Harford, 1982: Olden et al, 1982). Various lectins have been isolated from liver and macrophages (Stahl et al, 1976(Stahl et al, , 1978Kawasaki et al, 1978;Steer and Ashwell, 1980;Stockert et al, 1980;Sahagian et al, 198 1 ;Maynard and Baenziger, 1982;Mori et al, 1983;Wild et al, 1983;Gabius et al, 1984;Roche et al, 1985). It has been suggested that proteins with carbohydrate binding properties of different specificities exist in the CNS (Kobiler and Barondes, 1977;Simpson et al, 1977;Gremo et al, 1978).…”
mentioning
confidence: 99%
“…In contrast to this, human rhabdomyosarcoma cells revealed Ca 2+ ‐independent adhesion 38. Accordingly they adhere both on the pp‐AAc layers and on the hydrophobic CHF 3 plasma layers.…”
Section: Resultsmentioning
confidence: 72%
“…As provided therein, the sequence of the full-length cDNA including the first exon (two amino acids; methionine and alanine) is identical to the respective GenBank entries XM_00123499.2 (mRNA) and XM_00123499.2 (protein) and is also completely in line with the genomic sequence (Gene ID 425107). Following purification by affinity chromatography on lactosylated Sepharose 4B as a crucial step, controls for purity and activity assays were performed as described elsewhere (Gabius et al, 1984;Kaltner et al, 2008;Amano et al, 2012;André et al, 2012). Production and quality controls of CG-1A, Sequence alignment of CG-2 with (a) those of human galectin-1 and galectin-2 (hGal-1 and hGal-2) and (b) those of the other two prototype CGs (CG-1A and CG-1B).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%